Caught Between “Mundane West And Medieval Orient”: On The Origins And Implications Of The Balkan Collection in the Museum Europäischer Kulturen In Berlin - Thaden, Matthias (Lidé města, 2024)
From 1935 to 1939, Gustav Adolf Küppers embarked on ethnographic collecting trips throughout the Balkans, aiming to preserve what he deemed threatened “native culture”. His acquisitions, now housed in the Museum of European Cultures (Museum Europäischer Kulturen – Staatliche Museen zu Berlin, MEK), reflect both the museum’s interest and ethnography’s interest in regions well within Europe. While Küppers‘s trips were selfinitiated, questions arise about the ideological and political influences behind his collecting practices. Despite lacking colonial contexts in a constitutional sense, scrutiny of the collection‘s provenance and its representation of the region is crucial. Thus, the text aims to both enhance and contextualize our knowledge about Küppers‘s motivations, the museum‘s objectives, and the ideological currents at play.